Avancées récentes de la recherche sur l`intérêt de l`hydrogène dans le domaine de l`exercice : modulation du rythme circadien, l`immunité et la récupération de l`athlète - Todorovic, N.; Ostojic, S. M. (Science & Sports, 2025)
Objectives Molecular hydrogen (H2, dihydrogen) has gained significant attention in the scientific community due to its potential therapeutic properties. This review aims to critically evaluate H2's capacity to enhance athletes` immune function, modulate circadian rhythm, and facilitate recovery from exercise-induced fatigue.